Development of N-(4-(1H-Imidazol-1-yl)phenyl)-4-chlorobenzenesulfonamide, a Novel Potent Inhibitor of β-Catenin with Enhanced Antitumor Activity and Metabolic Stability - Puxeddu, Michela; Ling, Lele; Ripa, Silvia; D'Ambrosio, Michele; Nalli, Marianna; Parisi, Anastasia; Sciò, Pietro; Coluccia, Antonio; Granese, Arianna; Santelli, Martina; Masci, Domiziana; Cuřínová, Petra; et al. (Journal of medicinal chemistry, 2024)
The potential as a cancer therapeutic target of the recently reported hotspot binding region close to Lys508 of the β-catenin armadillo repeat domain was not exhaustively explored. In order to get more insight, we synthesized novel N-(heterocyclylphenyl)benzenesulfonamides 6-28. The new compounds significantly inhibited Wnt-dependent transcription as well as SW480 and HCT116 cancer cell proliferation. Compound 25 showed binding mode consistent with this hotspot binding region. Compound 25 inhibited the growth of SW480 and HCT116 cancer cells with IC50's of 2 and 0.12 μM, respectively, and was superior to the reference compounds 5 and 5-FU. 25 inhibited the growth of HCT-116 xenografted in BALB/Cnu/nu mice, reduced the expression of the proliferation marker Ki67, and significantly affected the expression of cancer-related genes. After incubation with human and mouse liver microsomes, 25 showed a higher metabolic stability than 5. Compound 25 aims to be a promising lead for the development of colorectal cancer anticancer therapies.
Keywords: Microsomes, Liver; nádorové buněčné linie; Xenograft Model Antitumor Assays; Mice, Inbred BALB C; HCT116 buňky; Mice; Cell Proliferation; Cell Line, Tumor; HCT116 Cells; Antineoplastic Agents; sulfonamidy; beta Catenin; Mice, Nude; xenogenní modely - testy protinádorové aktivity; Sulfonamides; protinádorové látky; zvířata; vztahy mezi strukturou a aktivitou; Humans; myši nahé; myši inbrední BALB C; myši; proliferace buněk; jaterní mikrozomy; beta-katenin; Structure-Activity Relationship; lidé; Animals